Practical Synthesis and Field Application of the Synthetic Sex Pheromone of Rice Stem Borer, Chilo suppressalis (Lepidoptera: Pyralidae) - Bin Liu; Kun-Jie Syu; Yuan-Xin Zhang; Sachin Gupta; Yu-Jhe Shen; Wei-Jynn Chien; Jui-Chang Tseng; Da Wei Lou (Journal of Chemistry)
Rice stem borer, Chilo suppressalis, is a common and major serious pest of rice, maize, and wheat crops across Asia, Europe, and Oceania countries. Its sex pheromone consists of three analogously compounds, i.e., (Z)-hexadec-11-enal (1), (Z)-octadec-13-enal (2), and (Z)-hexadec-9-enal (3), as long-chain aliphatic internal cis-alkenyl aldehydes. In order to perform an economic and widespread pest control management of rice stem borer, a versatile and efficient synthetic strategy is required. A versatile and efficient synthesis using a common synthetic route for cis-alkenals with high overall yields is described. Commercially available inexpensive aliphatic diols were chosen as starting materials. Two key steps were employed to synthesize the long-chain aliphatic internal cis-alkenes in excellent yields, including the alkylation of terminal alkynes without the utilization of a highly polar aprotic cosolvent and the versatile cis-selective semihydrogenation for the reduction of internal alkynes with excellent stereoselectivity. The results of field tests showed that the synthetic sex pheromone blend was highly effective for the capture of rice stem borer.